1996
DOI: 10.1182/blood.v88.3.1084.bloodjournal8831084
|View full text |Cite
|
Sign up to set email alerts
|

Active involvement of catalase during hemolytic crises of favism

Abstract: The endemic occurrence of favism in certain Mediterranean regions provided an investigative opportunity for testing in vivo the validity of claims as to the role of catalase in protecting human erythrocytes against peroxidative injury. Reduced activity of catalase was found in the erythrocytes of six boys who were deficient in erythrocytic glucose- 6-phosphate dehydrogenase (G6PD) and who were studied while suffering hemolysis after ingesting fava beans. Activity of catalase was further reduced when their red … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
1
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 0 publications
0
8
1
1
Order By: Relevance
“…Previous in vitro studies demonstrated the importance of NADPH in maintaining antioxidant enzymes, such as catalase (Scott et al, 1993). Gaetani et al (1996) reported a decrease in catalase levels and reduced glutathione in red blood cells with G6PD deficiency during hemolytic crises. Therefore, it was expected that erythrocyte with G6PD deficiency would show a greater susceptibility to damage caused by reactive oxygen species, since there would be less maintenance of NADPH-dependent enzymes, such as catalase and glutathione reductase in G6PDdeficient individuals without hemolytic crisis.…”
Section: Discussionmentioning
confidence: 99%
“…Previous in vitro studies demonstrated the importance of NADPH in maintaining antioxidant enzymes, such as catalase (Scott et al, 1993). Gaetani et al (1996) reported a decrease in catalase levels and reduced glutathione in red blood cells with G6PD deficiency during hemolytic crises. Therefore, it was expected that erythrocyte with G6PD deficiency would show a greater susceptibility to damage caused by reactive oxygen species, since there would be less maintenance of NADPH-dependent enzymes, such as catalase and glutathione reductase in G6PDdeficient individuals without hemolytic crisis.…”
Section: Discussionmentioning
confidence: 99%
“…Glucose-6-phosphate dehydrogenase (G6PD, E.C. 1.1.1.49) is a metabolic enzyme that catalyzes the first and rate-limiting step of the pentose phosphate pathway, converting d -glucose-6-phosphate (G6P) to 6-phosphoglucono-δ-lactone and producing the reduced form of nicotinamide adenine dinucleotide phosphate (NADPH) [1] , which plays a critical role in protecting cells against oxidative stress by regulating the levels of reduced glutathione [2] . G6PD is particularly important in erythrocytes because it is the sole production source of reducing equivalents.…”
Section: Introductionmentioning
confidence: 99%
“…The INS gene encodes insulin, which increases cell permeability to fatty acids and accelerates the pentose phosphate cycle for NADPH production in the liver ( 56 , 57 ). The CAT gene encodes catalase, a crucial scavenger of hydrogen peroxide in human erythrocytes, which is dependent on the availability of PPP-derived NADPH ( 58 ). NADPH is known to be tightly bound to mammalian catalase, and prevents inactivation of catalase by H 2 O 2 ( Fig.…”
Section: Discussionmentioning
confidence: 99%